PERANCANGAN VIDEO MOBIL ANTIK PRESIDEN IR. SOEKARNO SEBAGAI MEDIA UNTUK MENGENALKAN KEPADA MASYARAKAT SURABAYA - Muharram, Farid; Riyanto, Darwin Yuwono; cinantya, ixsora gempita (Jurnal Art Nouveau, 2017)
President Ir. Soekarno is a hero who inspired many people in Indonesia. But many people is unknowning about a precious objects relics of President Ir. Soekarno, for example found 23 units of antique presidential car ever used by President Ir. Soekarno to lead him to carry out his duties as a leader of the Indonesian state. In fact, not all of people, especially of Surabaya know what antique car ever used by President Ir. Soekarno in his tenure. This is based on the results of interviews conducted by several collectors who became resource persons. Lack of knowledge on President Ir. Sukarno led to low public awareness, especially in Surabaya about Presidential antique presidential car. Sukarno. From that case, this research is aimed to make a video of antique car of President Ir. Soekarno as a media to introduce to the people in Surabaya.Keyword: Video, Presiden Ir. Soekarno, Mobil Antik